2021
DOI: 10.1080/15298868.2021.1950828
|View full text |Cite
|
Sign up to set email alerts
|

Dual-centric work/family identity in young adults

Abstract: In the present study, we studied young adults who think work and family are equally and highly central -those with dual-centric work/ family identities. Using a mixed-method approach, we explored their characteristics, costs, benefits, and strategies of dual-centric work/family identities. The sample consisted of 124 participants, of which 36 participants (50% female) had dual-centric work/family identities. They reported higher levels of work satisfaction compared to those without dual-centric identities. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Family and work domains are vital aspects of the adult identity (Kemph, 1969). Research has shown how identification with work and family had positive implications on several outcomes (i.e., according to the above-mentioned social cure perspective; e.g., Svensson & Frisén, 2021). In line with the identity integration perspective, however, it is binding to analyze how these identifications are perceived as blended and compatible versus conflictual and incompatible, particularly in the context of stressful situations, challenging the interplay among people's roles (Manzi et al, 2021).…”
Section: Parent-work Identity Integration and Workers' Outcomesmentioning
confidence: 99%
“…Family and work domains are vital aspects of the adult identity (Kemph, 1969). Research has shown how identification with work and family had positive implications on several outcomes (i.e., according to the above-mentioned social cure perspective; e.g., Svensson & Frisén, 2021). In line with the identity integration perspective, however, it is binding to analyze how these identifications are perceived as blended and compatible versus conflictual and incompatible, particularly in the context of stressful situations, challenging the interplay among people's roles (Manzi et al, 2021).…”
Section: Parent-work Identity Integration and Workers' Outcomesmentioning
confidence: 99%
“…Множественность социокультурной идентичности определяет наличие научного интереса к пересечению, смешиванию, взаимовлиянию разных видов групповой идентичности. Например, исследование Y. Svensson и A. Frisén посвящено изучению взаимосвязи профессиональной и семейной идентичности в ранней взрослости [21], O. Spiegler с коллегами проследили взаимосвязь религиозной и национальной идентичности среди мусульман-мигрантов [22], C. Yea-Wen и M. Marion установили уровень слияния социальной и личностной идентичности, которое приводит личность к готовности пожертвовать собой ради группы [15].…”
Section: обзор литературыunclassified
“…Therefore, despite living in poverty, they are capable to overcome any challenge and change themselves. This belief is motivated by the responsibilities of a mother, arising after their life changes from being single into having a family and children (Kroger, 2015) while participating to earn a living-which is actually a father's duty (Svensson & Frisén, 2021).…”
Section: My Life As Their Mother We Won't Be Poor Forever If We Keep ...mentioning
confidence: 99%